Prevention of colitis in rats receiving palm oil on the background of dysbiosis by using quertulin - A. V. Bocharov; A. P. Levitsky; A. I. Gozhenko (Kazimierz Wielki University, 2017)
Aim: Identify the possibility of preventing colitis that develops in rats when consuming palm oil against dysbiosis. Materials and Methods: Antidysbiosis agent "Quertulin" (Quercetin + Inulin + Citrate Ca) was used. Biological experiments were performed on rats receiving a non-fat diet (NFD). The second group of rats received a diet in which 15% of starch was replaced with 15% palm oil containing 42% palmitic acid (C16:0). The third group of rats received a diet of palm oil and, in addition, received quertulin 400 mg / kg daily for 38 days. Rats of the 2nd and 3rd groups for development of dysbiosis from the first day of the experiment received lincomycin (60 mg / kg) with drinking water for 5 days. The activity of elastase, catalase, urease, lysozyme and the content of malodialdehyde (MDA) was determined in the gut mucosal homogenates. The ratio of catalase and MDA was calculated by the antioxidant-prooxidant index of API, according to the ratio of relative activity of urease and lysozyme - the degree of dysbiosis. Results: In rats receiving palm oil on the background of dysbiosis, the activity of elastase, urease, MDA content and the degree of dysbiosis increases in the mucosa of the colon, but the activity of catalase, lysozyme, and index API decreases. In rats receiving quertulin, the level of elastase, MDA, catalase, urease and lysozyme normalized, the API index increased and the degree of dysbiosis decreased. Conclusions: Consumption of palm oil on the background of dysbiosis causes the development of colitis and dysbiosis by reducing the level of nonspecific immunity and antioxidant protection. Antidysbiotic mean Quertulin has mucosoprotective action.